The need to eliminate mismanagement and corruption in Islamic social finance institutions - Hassan, Rusni; Muneeza, Aishath (IIUM Press, 2022)
During the COVID-19 pandemic, it became apparent that Islamic social finance (ISF) must be institutionalised due to inadequacies of Islamic commercial finance in providing adequate financial solutions to achieve financial inclusion. As such, the convergence of ISF with Islamic commercial finance is emerging while institutionalisation of ISF is gaining momentum globally. However, so far, there is no comprehensive governance code enacted to regulate the ISF institutions to guide them in the offering of their financial products and services within the parameters of Shari’ah, which include avoidance of corruption. Therefore, the objective of this research is to explore the existing mismanagement and corrupt practices found in managing the ISF and to recommend ways to overcome them. To meet its objective, this study adopts document analysis as its research methodology to review and discuss the selected management and corrupt practices of ISF institutions reported worldwide. It is anticipated that findings of this paper would assist policymakers, standard-setting bodies for Islamic finance, and ISF institutions to realise the significance of adopting good governance practices to take ISF to the next level. Further research could be undertaken to study the effectiveness of adopting good governance practices by ISF institutions and the implications of adopting such practices.